Encouraging Whistle Blowing to Improve Corporate Governance? A Malaysian Initiative - Shanthy Rachagan (Journal of business ethics, 2013)
This article reviews if the introduction of new laws to encourage and protect whistleblowers is sufficient to improve corporate governance in Malaysian public-listed companies. It provides suggestions to formulate internal whistle-blowing policies for companies. It concludes that due to the culture of the people and the taxonomy of Malaysian public-listed companies and companies in other countries in the Asia–Pacific region, having laws to encourage and protect whistleblowers to get rid of corporate wrong-doings is not necessarily the only solution. The article defines whistle blowing and the benefits of encouraging whistleblowers. It proceeds to highlight the issues of concern on whistle blowing. It also deliberates particular issues of whistleblowing in Malaysia by discussing the taxonomy of Malaysian public-listed companies, the strength of the regulators in enforcement, the Malaysian culture, and the Malaysian corporate scandals. The article elaborates on the whistle-blowing laws in Malaysia and concludes by providing alternate ways to encourage whistle blowing in Malaysian companies having in mind the taxonomy of Malaysian companies, enforcement by regulators and the Malaysian culture.